The Effect of Price and Taste Perception on Loyalty Mediated by Customer Satisfaction at Mixue Ice Cream & Tea Sumur Batu - Nadhila Adlina Sabila; Hendratmoko Hendratmoko (Syntax Idea)
The study aims to analyze the effect of price perception and taste on customer loyalty mediated by customer satisfaction at Mixue Ice Cream & Tea Sumur Batu. This research was conducted using the PLS-SEM method with the SmartPLS 4.0 program. The number of respondents used in this research were 100 respondents. The result of this research shows that price perception has positive and significant effect on customer satisfaction, taste has positive and significant effect on customer satisfaction, customer satisfaction has positive and significant effect on customer loyalty, price perception has positive and significant effect on customer loyalty, taste has positive and significant effect on customer loyalty, price perception has positive and not significant effect on customer loyalty mediated by customer satisfaction, taste has positive and significant effect on customer loyalty mediated by customer satisfaction